HUBUNGAN POSISI ERGONOMI PETANI DENGAN NYERI PINGGANG DI DESA KARANG TENGAH KABUPATEN JEMBER - Yugi Hari Chandra; Rizki Eko Prasetyo (Jurnal Kesehatan dr. Soebandi, 2017)
The agricultural sector is one type of work that has a high risk for workers. Extreme environmental conditions and the way and use of technology in managing land that is still traditional compared to other regions determine the level of health and safety of farmers. Ergonomics is the science, art and application of technology to harmonize or balance between all facilities used both in activity and rest with all abilities. The sampling technique used is the simple random sampling method. This study is a cross-sectional study. The population in this study was 80 respondents, a sample of 67 respondents. (0.05) which shows that there is a relationship between ergonomic position and low back pain in Karang Tengah Village, Jember Regency. This research shows that the role of occupational health nurses or Occupational Health Nursing (OHN) in agriculture must be increased